cDNA Clones Construction Of Dengue Virus Type-2 (New Guinea C-Strain) - Ong, Eng Keat (2009)
Dengue virus type-2 (DEN-2) is a member of the Flaviviridae family. DEN-2 has a single-stranded positive polarity ribonucleic acid (RNA) genome of 10,723 nucleotides in length that encodes for a single polyprotein precursor. In this work, viral RNA genome was extracted from Vero and C6/36 cells infected with DEN-2 New Guinea C strain. The viral RNA genome of DEN-2 was reverse transcribed and amplified as seven overlapping fragments, covering the whole genome, by reverse transcription-polymerase chain reaction (RT-PCR). Each of these fragments was successfully cloned into a high copy number plasmid, pGEMR- T vector and transformed into Escherichia coli (E. coli) JM109 strain. The identity of each clone was verified using DNA sequencing. The seven overlapping fragments were successfully joined together in pGEMR-T vector and transformed into E. coli JM109 strain at 25°C with the presence of ampicillin (25 pg/ml) to produce a cDNA clone carrying the full-length genome of DEN-2.